A introdução das Ciências Naturais no Pará por meio das instituições de ensino - BARROS, Jônatas Barros e (Universidade Federal do Pará, 2017)
The objective of this research is to analyze the process of introduction of science in Pará, through the schools, and the conditions that allowed this process. We resumed the Pombal reforms of the second half of the eighteenth century, which marked the introduction of the Modern Scientific Rationality in Portuguese Kingdom, where the Para was Cologne. They expelled the Jesuits by inserting a gap in education, which began to be filled with the creation of the College of Nobles, Reform at the University of Coimbra and implementation of Régias classes. At that stage the natural sciences were introduced only in the metropolis, while in Pará created classes that kept the dominance of Letters and Humanities. The Marquis of Pombal's reforms have made the most favorable educational environment paraense receptivity of Natural Sciences, mainly because of the nationalization of education. This became incisive from the second half of the 1830s Rulers of Pará suggested the introduction of scientific disciplines and educational models in effect in countries like France, which was a diffuser center of modernity. This began to be realized with the creation of Liceu Paraense in 1841, which was intended to provide secondary education. Ten years later, in 1851, he implanted the first time physics and chemistry, which was repeated twice more, in 1868 and 1873. In the first insertion Botany was also present, while in the latter, the Natural History. In 1871, the initial phase of the Belle Époque, a time when the entry of Modernity in Para was accelerating, Physics and Chemistry were continued in Escola Normal do Pará, created this year in order to train teachers to work in primary education, but only until 1872, when they were taken out of this institution. In 1890 they returned with more expressiveness, being represented by six Sciences. In primary education, the natural sciences also consisted, from 1870, motivating teachers in that sector the coursing Physics and Chemistry in the Escola Normal and Liceu Paraense. Thus, educational institutions were instrumental in the introduction of science in Pará, conditioned by the social context, first of Pombal reforms, culminating in the nationalization of education, and Belle-Époque, with the acceleration of Modernity entry in Pará. scientific presence in the curricula was marked by discontinuities in the initial phase, since the reception of the modernizing process, the local culture, had not yet made the learning of science is an imperative need. This began to happen from 1890 when the Science began to widen in school curricula.